APPLICATION OF TRADITIONAL CATFISH PEG GAMES IN LEARNING MATH ALGEBRA MATERIAL AT SMPN 10 BANDA ACEH - Murda Riski Murda Riski. G; Mulia Putra; Rahmatillah Rahmatillah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Many factors cause students' ability to learn mathematics to be low. Therefore it is very important to implement an innovative learning that is able to improve students' abilities in learning mathematics, one way that can be taken is to apply the catfish stake game in learning. Patok Lele is a game native to the archipelago which is spread in various regions of Indonesia including in Aceh Province, especially in Banda Aceh, the game Patok Lele is played in groups. The formulation of the problem in this study is whether the application of the traditional Patok Lele game affects the learning of mathematics in algebra material at SMPN 10 Banda Aceh. The aim of this research is to determine the application of the Traditional Patok game to learning mathematics in algebra material at SMPN 10 Banda Aceh. This research belongs to quantitative research, this research is an experimental research type and uses the One Group Pretest-Posttest Design. The results of the hypothesis analysis were carried out using the t pair sample statistical test. Based on the analysis using the t test, the value of t (count) = 21.641 is obtained and t_table = 1.70. So tcount>ttable , it can be concluded that the application of the Traditional Patok Lele game has an effect on learning mathematics in algebra material at SMPN 10 Banda Aceh. In implementing the Traditional Patok Lele game, teachers are expected to be able to look at the difficulties experienced by some students in each step of their learning so that they can immediately help them overcome.